Hubungan Posisi Kerja dengan Keluhan Nyeri Punggung Bawah pada Penjahit - Annissa, Annissa; Aulia, Arsya; Mathofani, Puji Eka (Universitas Faletehan, 2024)
Lower back pain is a common health problem encountered worldwide, leading to a decreased productivity and spinal function capacity. The prevalence of lower back pain varies annually with incidence rates ranging from 15 to 45%. This study aimed to identify the relationship between complaints of lower back pain, years of service, length of service, work position, stretching, and exercise habits. The research design utilized a cross-sectional approach. The study population consisted of all tailors at Pasar Raya Block F, totaling 35 tailors with the sample size of 35 individuals selected by using total sampling method. The data were analyzed by using univariate and bivariate analysis through chi-square test. The results indicated a correlation between work position (p value 0.000) and complaints of lower back pain. Whereas, no correlation was found between years of service (p value 0.565), length of service (p value 0.090), stretching (p value 0.070), and exercise habits (p value 0.712) with complaints of lower back pain. Tailors were encouraged to improve their work positions during their daily activities. Further research may explore other factors, such as the addition of seat cushions and body mass index (BMI) that may be associated with complaints of lower back pain among tailors.